2014
DOI: 10.1007/s11227-014-1251-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing in e-Science: research challenges and opportunities

Abstract: SOA (Service Oriented Architecture), workflow, the Semantic Web, and Grid computing are key enabling information technologies in the development of increasingly sophisticated e-Science infrastructures and application platforms. While the emergence of Cloud computing as a new computing paradigm has provided new directions and opportunities for e-Science infrastructure development, it also presents some challenges. Scientific research is increasingly finding that it is difficult to handle "big data" using tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 96 publications
0
20
0
8
Order By: Relevance
“…Next, all important reliability and HA measuring tools and metrics to evaluate the importance degree of each cloud components in the proposed architecture will be specified. Some main failure modes of CCSs have been proposed in [36,63,64] but as one of the future works of this research, different viewpoints exist for proposing a comprehensive classification of cloud failures. Table 4 presents a summary of these studies.…”
Section: Which?mentioning
confidence: 99%
“…Next, all important reliability and HA measuring tools and metrics to evaluate the importance degree of each cloud components in the proposed architecture will be specified. Some main failure modes of CCSs have been proposed in [36,63,64] but as one of the future works of this research, different viewpoints exist for proposing a comprehensive classification of cloud failures. Table 4 presents a summary of these studies.…”
Section: Which?mentioning
confidence: 99%
“…Out of these problems, cloud computing can help the EIs to reduce their financial and technical issues by providing servers, databases, software, Online library, etc. These facilities do not only help in reducing the expenses of EIs on purchasing new equipment like servers, databases, software, etc., but also in reducing the need for extra space, and manpower for operating and maintaining these systems [13]. For example, when it comes to deploy a network in an EI, then the equipment is purchased.…”
Section: Trust Management In Educational Institutesmentioning
confidence: 99%
“…In their paper, Yang, et al [13] gave the detailed survey of recent research advances in different fields and cloud computing in e-science. They included, e.g., business model, computing model, and programming model in e-science.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Strategic Outsourcing), or even multi-party contracts.Although several advances happened in the last years in the cloud space, there is still a lot to be done in HPC cloud. Studies have shown some challenges on HPC cloud [1,52,53,55,56,90,102,111,115,119], however, they do not present a comprehensive view of findings and challenges in the area. Therefore, this paper aims at helping users, research institutions, universities, and companies understand solutions in HPC cloud.…”
mentioning
confidence: 99%